2007
DOI: 10.1007/s00436-007-0824-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperprolactinaemia on Toxoplasma gondii prevalence in humans

Abstract: Recent studies have shown that hormones could induce anti-parasitic functions of the host immune system; thus, the aim of the present study was to estimate the seroprevalence of Toxoplasma gondii antibodies by an enzyme-linked immunosorbent assay in a Polish population of women and men with hyperprolactinaemia (n = 234) and hypoprolactinaemia (n = 41) and in a control group (n = 281) with the physiological level of prolactin (PRL). Women with hyperprolactinaemia revealed lower seroprevalence than those with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…Normalization of prolactin levels in patients with migraine found after treatment with VA (Horrobin, 1973;Murialdo & Polleri, 1987) could reflect beneficial effects of killing T. gondii tachyzoites by the drug rather than eventual prolactin role promoting VA efficacy (Horrobin, 1973;Serdaroglu et al, 2002). Recent findings that women with hyperprolactinemia have markedly lower seroprevalence of T. gondii antibodies than those with normal prolactin levels (33.9 vs. 45.58%, p < .025) (Dzitko, Malicki, & Komorowski, 2008) provided further support for this argument.…”
Section: Important Role Of Calcium In T Gondii Tachyzoites Invasion mentioning
confidence: 70%
“…Normalization of prolactin levels in patients with migraine found after treatment with VA (Horrobin, 1973;Murialdo & Polleri, 1987) could reflect beneficial effects of killing T. gondii tachyzoites by the drug rather than eventual prolactin role promoting VA efficacy (Horrobin, 1973;Serdaroglu et al, 2002). Recent findings that women with hyperprolactinemia have markedly lower seroprevalence of T. gondii antibodies than those with normal prolactin levels (33.9 vs. 45.58%, p < .025) (Dzitko, Malicki, & Komorowski, 2008) provided further support for this argument.…”
Section: Important Role Of Calcium In T Gondii Tachyzoites Invasion mentioning
confidence: 70%
“…Based on the literature (Benedetto et al 1995(Benedetto et al , 2001) and on our previous results (Dzitko et al 2008), different hypotheses on the potential antiparasitic action of the PRL were considered. Inhibition of tachyzoite proliferation after their pre-incubation with the PRL and lack of such effect when the hormone was added simultaneously with the parasites to host cells suggests that PRL interacts directly with toxoplasma cells.…”
Section: T Gondii Penetration and Parasitophorous Vacuole Formationmentioning
confidence: 99%
“…Hyperprolactinemia was described as an immunoregulatory factor in various parasite infestations (2,5,9). An in vitro study showed that exogenous recombinant According to these studies, a high level of PRL may be an important factor for preventing toxoplasmosis.…”
Section: Discussionmentioning
confidence: 96%